2021
DOI: 10.29392/001c.23621
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of non-communicable diseases and maternal and child health needs of Venezuelan migrants in South America

Abstract: BackgroundMigration of Venezuelan citizens to other South American countries has increased in recent years. While the prevalence, morbidity, and mortality of infectious diseases in Venezuelan migrants across South America appears to be well described, the non-communicable disease (NCD) and maternal and child health needs in this population is less clear. A scoping review of existing peer-reviewed primary research and grey literature describing the epidemiology of NCDs and maternal and child health needs in Ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…For example, Leung et al 85 found that migrant status was associated with an increased risk of hospitalizations for asthma and other wheezing disorders in Hong Kong children, afterwards Li et al 86 investigating the prevalence of asthma and allergic symptoms in Suzhou, China, found that domestic migrants had a higher prevalence of asthma than local residents and recently Cacciani et al 87 investigated potentially avoidable hospitalizations for asthma in children and adolescents by migrant status in Italy and found that children with migrant backgrounds had a higher risk of hospitalization. Similar observations have been reported in 2021 by the group of Gallo Marin, 88 with a scoping review of noncommunicable diseases and maternal and child health needs of Venezuelan migrants in South America, and the study observed that environmental factors, such as poor housing conditions and exposure to air pollution, may contribute to the development of asthma and allergies in this population. The role of farm environment was analysed by Timm et al 89 in a three‐generation cohort study in Denmark founding that selective migration from farming environments was associated with an increased risk of asthma, suggesting that changes in environmental exposures, such as decreased exposure to endotoxins and farm animals, may contribute to this increased risk.…”
Section: Migration Studiessupporting
confidence: 88%
“…For example, Leung et al 85 found that migrant status was associated with an increased risk of hospitalizations for asthma and other wheezing disorders in Hong Kong children, afterwards Li et al 86 investigating the prevalence of asthma and allergic symptoms in Suzhou, China, found that domestic migrants had a higher prevalence of asthma than local residents and recently Cacciani et al 87 investigated potentially avoidable hospitalizations for asthma in children and adolescents by migrant status in Italy and found that children with migrant backgrounds had a higher risk of hospitalization. Similar observations have been reported in 2021 by the group of Gallo Marin, 88 with a scoping review of noncommunicable diseases and maternal and child health needs of Venezuelan migrants in South America, and the study observed that environmental factors, such as poor housing conditions and exposure to air pollution, may contribute to the development of asthma and allergies in this population. The role of farm environment was analysed by Timm et al 89 in a three‐generation cohort study in Denmark founding that selective migration from farming environments was associated with an increased risk of asthma, suggesting that changes in environmental exposures, such as decreased exposure to endotoxins and farm animals, may contribute to this increased risk.…”
Section: Migration Studiessupporting
confidence: 88%
“…Migration under these conditions is associated with significant challenges. Many experience physical hardships, emotional stress, physical violence, food insecurity, and other exposures and many have only limited or no access to health care, all of which can negatively impact their health and well-being [ 11 – 14 , 27 , 28 ]. Pregnant refuges and other immigrants are particularly vulnerable to the effects of migration-related stressor which can affect their access to maternal care services and negatively affect maternal-fetal outcomes [ 15 – 17 ].…”
Section: Discussionmentioning
confidence: 99%